Process for preparing Ziegler-Natta catalysts for polymerization of low density copolymers

By preparing a magnesium support in branched chain alkyl alcohols or cycloalkyl alcohols and adding titanium compounds to form a Ziegler-Natta catalyst, the problems of sensitive catalyst preparation conditions and impurities in the prior art are solved, and efficient production is achieved Low-density copolymer with excellent physical properties.

CN119317651APending Publication Date: 2025-01-14SK INNOVATION CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380047923.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-05-10
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing Ziegler-Natta catalyst preparation methods have problems with sensitive preparation conditions and impurity generation, which leads to unsuitable for large-scale production of uniformly distributed low-density copolymers.

Method used

In the presence of branched chain alkyl alcohols or cycloalkyl alcohols, a magnesium support is prepared by reacting dialkyl magnesium with an alkylaluminum compound, and a metal compound containing titanium is added to the magnesium support solution to form excellent catalytic activity Ziegler-Natta catalyst.

Benefits of technology

The productivity of the catalyst and the yield of low-density copolymers are significantly improved, the physical properties of the copolymers are improved, especially the elongation and utilization, and the opacity and low solubility of the magnesium support solution help to improve catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317651A_ABST
    Figure CN119317651A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a Ziegler-Natta catalyst for polymerization of a low density copolymer, and specifically, to a method for preparing a Ziegler-Natta catalyst comprising preparing a magnesium support by reacting an alkyl aluminum compound in the presence of a branched alkyl alcohol or cycloalkyl alcohol solvent. Since the Ziegler-Natta catalyst prepared by the method for preparing the Ziegler-Natta catalyst according to one embodiment has excellent catalytic activity, a low-density copolymer which can have various physical properties and excellent copolymerization performance can be efficiently produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a Ziegler-Natta catalyst for polymerization of a low-density copolymer, and a method for producing a low-density copolymer using the Ziegler-Natta catalyst prepared thereby. Background Art

[0002] Ziegler-Natta (Z / N) type polymerization catalysts are catalysts used to produce olefin polymers (e.g., ethylene copolymers). Typically, Ziegler-Natta catalysts contain a magnesium compound, an aluminum compound, and a titanium compound supported on a specific carrier.

[0003] Since the shape and size of polymers polymerized using Ziegler-Natta catalysts depend on the catalyst used, it is important to prepare a catalyst that can increase throughput and produce uniformly distributed polymers.

[0004] Although a lot of development work has been done on the preparation of Ziegler-Natta catalysts, some methods are not suitable for large-scale preparation of catalysts due to significant sensitivity to preparation conditions or the generation of large amounts of impurities or waste. U.S. Patent No. 8,003,741 discloses a method for preparing a Ziegler-Natta catalyst, in which a magnesium compound is dissolved in an alcohol and then a titanium compound is added, but the preparation process is complex and the types of materials used are many. Summary of the invention

[0005] Technical issues

[0006]

[0013] Embodiments of the present invention provide a method for preparing a Ziegler-Natta catalyst for the polymerization of low density copolymers.

[0007] Another embodiment of the present invention provides a Ziegler-Natta catalyst for polymerization of a low-density copolymer, which is prepared by the preparation method according to the embodiment.

[0008] Still another embodiment of the present invention provides a method for producing a low-density copolymer using the Ziegler-Natta catalyst for polymerization of a low-density copolymer according to the embodiment.

[0009] Technical solutions to technical problems

[0010] In one general aspect, a method for preparing a Ziegler-Natta catalyst for polymerization of a low density copolymer includes: adding a branched alkyl alcohol or a cycloalkyl alcohol to a mixture of a dialkyl magnesium and a compound represented by the following Chemical Formula 1 to prepare a solution containing a magnesium support; and

[0011] Adding a metal compound containing titanium (Ti) to a solution containing a magnesium support:

[0012] [Chemical formula 1]

[0013] R 1 x AlCl 3-x

[0014] In Chemical Formula 1,

[0015] Each R 1 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and

[0016] x is 1 to 3.

[0017] In another general aspect, provided is a Ziegler-Natta catalyst for polymerization of a low-density copolymer, which is prepared by the method for preparing a Ziegler-Natta catalyst for polymerization of a low-density copolymer according to the embodiments.

[0018] In yet another general aspect, a method for producing a low density copolymer includes contacting an olefin monomer with a Ziegler-Natta catalyst for polymerization of a low density copolymer according to an embodiment.

[0019] Advantageous Effects of the Invention

[0020] The present invention relates to a method for preparing a Ziegler-Natta catalyst for polymerization of a low-density copolymer, and in particular, to a method for preparing a Ziegler-Natta catalyst, which comprises preparing a magnesium support by reacting an alkyl aluminum compound in the presence of a branched alkyl alcohol or cycloalkyl alcohol solvent. Since the Ziegler-Natta catalyst prepared by the method for preparing a Ziegler-Natta catalyst according to one embodiment has excellent catalytic activity, a low-density copolymer having various physical properties and excellent copolymerization performance can be effectively produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A graph showing the results of analyzing polymers produced using the Ziegler-Natta catalyst prepared in Examples and a commercially available catalyst by crystallization elution fractionation (CEF).

[0022] Figure 2 The diagram shows the results of observing the forms of the magnesium support solutions prepared in Examples 1-4, 3-4, 4-4, 5-4 and 6-4 and Comparative Examples 1-4, 2-4 and 3-4 through photographs.

[0023] Figure 3 The diagram shows the results of observation of the forms of the magnesium support solutions prepared in Examples 1 to 4 and the prepared catalysts through photographs. DETAILED DESCRIPTION

[0024] The embodiments disclosed in this specification can be modified into various forms, and the technology according to the embodiments is not limited to the embodiments described below. In addition, throughout the specification, unless otherwise explicitly stated, "comprising" any component will be understood to mean including other components rather than excluding any other components.

[0025] The numerical range used in this specification includes upper and lower limits and all values ​​within these upper and lower limits, increments of form and span logical deduction within the limited range, all double limit values, and all possible combinations of upper and lower limits within the numerical range defined in different forms. For example, when the content of the composition is limited to 10% to 80% or 20% to 50%, the numerical range of 10% to 50% or 50% to 80% should also be understood as described in this specification. Unless otherwise specifically defined in this specification, values ​​that may appear outside the numerical range due to experimental errors or rounding of numerical values ​​also fall within the defined numerical range.

[0026] Hereinafter, unless expressly defined otherwise in this specification, “about” may be considered to be a value within 30%, 25%, 20%, 15%, 10% or 5% of a stated value.

[0027] Hereinafter, "alkyl" in this specification is defined as being able to represent both alkyl and cycloalkyl. In addition, even if there is no specific definition, alkyl or cycloalkyl can also be interpreted as including derivatives that are expected to exert similar effects and that can be easily modified by those skilled in the art, or alkyl or cycloalkyl substituted with general substituents (e.g., halogen, etc.).

[0028] According to the method for preparing Ziegler-Natta catalyst of the embodiment of the present invention, comprising reacting dialkyl magnesium with alkyl aluminum compound in the presence of branched alkyl alcohol and / or cycloalkyl alcohol solvent, a method for preparing Ziegler-Natta catalyst for polymerization of low-density copolymer can be provided, and the catalyst has significantly improved catalytic activity. In the case of using the Ziegler-Natta catalyst prepared by the preparation method of Ziegler-Natta catalyst according to the embodiment to polymerize low-density copolymer, the catalyst productivity (catalyst mileage) can be significantly higher than the catalyst productivity of conventional catalysts prepared by using straight-chain alkyl alcohol such as n-propanol as solvent. In addition, compared to commercial products, the low-density copolymer polymerized using the Ziegler-Natta catalyst according to the embodiment of the present invention has a low proportion of high-density regions (homopolymers) and a high proportion of low-density regions (copolymers), so that the low-density copolymer has a higher elongation (elongation) and excellent utilization (utilization). The preparation method of the Ziegler-Natta catalyst for polymerization of low-density copolymer according to the embodiment and the polymerization of low-density copolymers using the catalyst are described in detail below.

[0029] The embodiment provides a method for preparing a Ziegler-Natta catalyst for polymerization of a low-density copolymer, the method comprising: adding a branched alkyl alcohol and / or a cycloalkyl alcohol to a mixture of a dialkyl magnesium and a compound represented by the following Chemical Formula 1 to prepare a solution containing a magnesium carrier (magnesium carrier solution); and

[0030] Adding a metal compound containing titanium (Ti) to a solution containing a magnesium support:

[0031] [Chemical formula 1]

[0032] R 1 x AlCl 3-x

[0033] In Chemical Formula 1,

[0034] Each R 1 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and

[0035] x is 1 to 3.

[0036] According to the preparation method of the embodiment, dialkyl magnesium and alkyl aluminum represented by Chemical Formula 1 react with each other in the presence of a branched alkyl alcohol or cycloalkyl alcohol solvent, thereby a Ziegler-Natta catalyst with excellent catalytic activity can be prepared. Therefore, in the case of using the Ziegler-Natta catalyst prepared according to the embodiment to polymerize a low-density copolymer, the low-density copolymer can be produced with significantly increased yield and / or catalyst productivity. In addition, since the catalyst has excellent comonomer reactivity, compared to commercially available straight-chain low-density copolymers produced by conventional techniques, the low-density copolymer produced using the catalyst has a high proportion of low-density regions, and therefore can have excellent physical properties such as high elongation.

[0037] Unlike conventional magnesium carrier solutions, the solution (or magnesium carrier slurry solution) containing magnesium carrier prepared by the preparation method of Ziegler-Natta catalyst according to the embodiment is opaque, that is, compared with conventional transparent magnesium carrier solution, it has lower solubility. According to the magnesium carrier solution of the embodiment, because it has such solubility characteristics, significant catalytic activity can be achieved. Specifically, the magnesium carrier according to the embodiment can significantly and effectively contribute to achieving high catalytic activity because its physical properties are very stable. In addition, in the magnesium carrier according to the embodiment, since the transition metal is loaded on the outside of the magnesium carrier, the active sites of the transition metal are increased, thereby significantly increasing the catalytic activity. On the other hand, in the conventional transparent magnesium carrier solution (Comparative Example 1) prepared, the magnesium carrier and the catalyst are coprecipitated (coprecipitated) to form an incomplete support (incomplete support), and since the transition metal is loaded on the inside and outside of the carrier, the active sites of the transition metal are reduced, thereby reducing the catalytic activity.

[0038] The effect achieved in the above embodiment can be achieved by using branched alkyl alcohol and / or cycloalkyl alcohol as solvent in the process of preparing magnesium carrier solution. The preparation of the solution containing magnesium carrier is the step of magnesium and alcohol forming a complex, in which case the alkyl group of the alcohol may be an important factor in the formation of the complex. In one embodiment, aluminum trialkoxides in the form of trimer (trimer) can be formed by using branched alkyl substituted alcohol or cyclic alkyl substituted alcohol, with the result that when forming magnesium-alcohol complex, aluminum trialkoxides can also agglomerate with each other to form an insoluble slurry.

[0039] In one embodiment, the dialkyl magnesium may be each independently a linear or branched C 1-10 Alkyl or C 3-10 Alternatively, the dialkyl magnesium may be selected from two independently selected C1-6 Alkyl, C 1-5 Alkyl, C 2-5 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl and C 5-6 In one embodiment, the dialkyl magnesium may be ethyl-n-butyl magnesium (BEM) (Et(n-Bu)Mg).

[0040] In one embodiment, the magnesium support may include an adduct or complex of magnesium and an alcohol and / or an alkyl group. For example, the magnesium support may be composed of Mg(OR)2·a[Al b (OR) 3b ] In this case, a may be, for example, 0.1 to 10, 0.1 to 6, 0.5 to 6, 0.5 to 3, 0.8 to 2, 0.8 to 1.5 or 1. In addition, b may be, for example, 0.1 to 10, 0.1 to 6, 0.1 to 5, 0.1 to 3, 0.1 to 1, 0.2 to 0.8 or 0.5. For example, the magnesium carrier may be Mg(OR)·[Al 0.5 (OR) 1.5 ]. In addition, R may be, for example, an alkyl group derived from an alcohol, and thus R may be a branched alkyl group or a cycloalkyl group.

[0041] In one embodiment, R 1 Each of them can be a straight chain or branched chain C 1-6 Alkyl, C 1-5 Alkyl, C 1-3 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, -CH(CH3)CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl or C 5-6 Cycloalkyl, in which case all R 1 can be the same substituent. However, this is just an example, R 1 It is not limited to this.

[0042] In one embodiment, x may be, for example, 1, 3 / 2, 2, 5 / 2 or 3. Specifically, the compound represented by Chemical Formula 1 may be a trialkylaluminum (R 1 3Al), wherein x is 3. In one embodiment, the compound represented by Chemical Formula 1 may be triethylaluminum (C6H 15 Al) or tributylaluminum (C 12 H 27 Al) (or triisobutylaluminum).

[0043] The preparation method according to the embodiment can be carried out in the presence of a general organic solvent, for example, 5-20 The reaction is carried out in the presence of a saturated hydrocarbon solvent. Specifically, pentane, hexane, heptane, octane, nonane, decane or a mixed solvent thereof can be used.

[0044] The preparation method according to the embodiment may further include, after adding the metal compound, adding a compound represented by the following Chemical Formula 2:

[0045] [Chemical formula 2]

[0046] R 2 y AlCl 3-y

[0047] In chemical formula 2,

[0048] Each R 2 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and

[0049] y is 1 to 2.

[0050] In this case, R 2 Each can be independently a linear or branched C 1-6 Alkyl, C 1-5 Alkyl, C 2-5 Alkyl, -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CH2CH3, C 3-6 Cycloalkyl, C 4-6 Cycloalkyl or C 5-6 Cycloalkyl, in which case all R 2 can be the same substituent. However, this is just an example, R 2 It is not limited to this.

[0051] In one embodiment, y can be, for example, 0, 1 / 2, 1, 3 / 2, or 2.

[0052] In one embodiment, the compound represented by Chemical Formula 2 may be ethylaluminum sesquichloride (C6H 15 Al2Cl3, also known as (C2H5) 3 / 2 AlCl 3 / 2 ), ethylaluminum dichloride (EtAlCl2), methylaluminum dichloride (MeAlCl2), propylaluminum dichloride (PrAlCl2) or butylaluminum dichloride (BuAlCl2), one or more compounds may be used simultaneously or in combination. In one embodiment, the alkylaluminum chloride compound represented by Chemical Formula 2 may be a monomer or a dimer.

[0053] In one embodiment, the molar ratio of the metal compound to the compound represented by Chemical Formula 2 may be 1:0.1 to 1:15, 1:0.1 to 1:10, 1:1 to 1:10, 1:2 to 1:10, 1:2 to 1:8, 1:3 to 1:5, or about 1:5. However, this is just an example, and the molar ratio is not limited thereto.

[0054] In one embodiment, the molar ratio of the metal compound to the magnesium support may be 1:5 to 1:30, 1:5 to 1:30, 1:10 to 1:30, 1:10 to 1:25, 1:10 to 1:20, 1:12 to 1:18, or about 1: 15. However, this is just an example, and the molar ratio is not limited thereto.

[0055] In one embodiment, the metal compound may further contain a transition metal, for example, a Group IV or Group V metal. Specifically, the metal compound may further contain one or more metals selected from the group consisting of Zr, Hf, V, Nb, and Ta. In this case, the metal may exist in the form of chloride, alkoxy chloride, alkylate, etc., however, this is only an example, and the metal is not limited thereto.

[0056] In one embodiment, the metal compound containing titanium (Ti) may contain TiX4 or (R 3 O) z Ti(X) 4-z In this case, X is a halogen atom such as I, Br, Cl or F, and each R 3 are independently linear or branched C 1-10 Alkyl, C 1-8 Alkyl, C 2-6 Alkyl or C 1-5 alkyl, z is an integer of 1 to 4 (e.g., 1, 2, 3 or 4). Specific examples of the metal compound include TiCl4, TiBr4, TiI4, Ti(OBu)4, Ti(Oi-Pr)4, Ti(OEt)4, Ti(OEt)2(Cl)2 and Ti(OEt)(Cl)3. However, this is just an example, and the metal compound is not limited thereto.

[0057] In one embodiment, the metal compound containing titanium (Ti) may be a mixed metal compound further comprising a Group V metal compound. For example, the metal compound according to the embodiment may be a mixed metal compound of a metal compound containing titanium (TiCl4) and a Group V metal compound containing a Group V metal (VOCl3).

[0058] In one embodiment, the mole number of the added branched alkyl alcohol or cycloalkyl alcohol can exceed one time of the mole number of dialkyl magnesium. For example, the mole number of the added branched alkyl alcohol or cycloalkyl alcohol can be more than 1.2 times, more than 1.5 times, more than 2.0 times, less than 10 times, less than 8 times, less than 5 times, less than 4 times or less than 3.5 times the mole number of dialkyl magnesium. Alternatively, the molar ratio of dialkyl magnesium to branched alkyl alcohol or cycloalkyl alcohol can be 1:1.2 to 1:10, 1:1.5 to 1:10, 1:1.5 to 1:8, 1:1.5 to 1:6, 1:1.5 to 1:5, 1:2 to 1:8, 1:2 to 1:4 or 1:1.5 to 1:3.5.

[0059] In one embodiment, the mole number of the added branched alkyl alcohol or cycloalkyl alcohol may exceed twice the mole number of the compound represented by Chemical Formula 1. For example, the mole number of the added branched alkyl alcohol or cycloalkyl alcohol may be 2.2 times or more, 2.5 times or more, 3 times or more, 4 times or more, 10 times or less, 9 times or less, 8 times or less, or 7 times or less of the mole number of the compound represented by Chemical Formula 1. Alternatively, the molar ratio of the compound represented by Chemical Formula 1 to the branched alkyl alcohol or cycloalkyl alcohol may be 1:2.5 to 1:10, 1:2.5 to 1:9, 1:2.5 to 1:8, 1:2.5 to 1:7, 1:3 to 1:10, or 1:4 to 1:10.

[0060] In one embodiment, the addition of the branched alkyl alcohol or cycloalkyl alcohol can be carried out at a temperature of about 10° C. to -50° C., 0° C. to -30° C., -5° C. to -25° C., or -10° C. to -20° C. In addition, after adding the branched alkyl alcohol or cycloalkyl alcohol, the step of allowing the reaction to proceed can be carried out for about 120 minutes to 300 minutes, 180 minutes to 300 minutes, 200 minutes to 300 minutes, 220 minutes to 260 minutes, or about 240 minutes.

[0061] The branched alkyl alcohol according to the embodiment is not particularly limited as long as it is an alcohol substituted with a branched alkyl group, and examples thereof may include branched C 3-20 Alkyl alcohol, branched chain C 3-15 Alkyl alcohol, branched chain C 3-10 Alkyl alcohol, branched chain C 3-8 Alkyl alcohol, branched chain C 3-6 Alkyl alcohol, branched chain C 3-5 Alkyl alcohol or branched C 3-4Alkyl alcohol. As a specific example, the branched alkyl alcohol can be isopropanol, isobutyl alcohol, tert-butyl alcohol, sec-butyl alcohol, 2-pentanol, 2-methyl-1-butanol, 3-methyl-1-butanol, 3-pentanol, neopentyl alcohol, 2-methyl-2-butanol, 3-methyl-2-butanol, 2-hexanol, 3-hexanol, 2-methyl-1-pentanol, 3-methyl-1-pentanol, 4-methyl-1-pentanol, 2-methyl-2-pentanol, 3-methyl-2-pentanol, 4-methyl-2-pentanol, 2-methyl-3-pentanol, 3-methyl-3-pentanol, 2,2-dimethyl-1-butanol, 2,3-dimethyl-1-butanol, 3,3-dimethyl-1-butanol, 2,3-dimethyl-2-butanol, 3,3-dimethyl-2-butanol, 2-ethyl-1-butanol or a combination of two or more thereof. Furthermore, the above alcohol is just an example and is not limited as long as it is an alcohol having a branched alkyl chain.

[0062] The cycloalkyl alcohol according to the embodiment is not particularly limited as long as it is an alcohol substituted with a cycloalkyl group, and can be C 3-20 Cycloalkyl alcohol, C 3-15 Cycloalkyl alcohol, C 3-10 Cycloalkyl alcohol, C 3-8 Cycloalkyl alcohol, C 3-6 Cycloalkyl alcohol, C 4-6 Cycloalkyl alcohol or C 5-6 Cycloalkyl alcohol. As a specific example, cycloalkyl alcohol can be cyclopropyl alcohol, cyclobutanol, cyclopentanol, cyclohexanol, cycloheptanol, cyclooctanol, cyclononanol, cyclodecyl alcohol, bicyclo [2.1.1] hexanol, bicyclo [2.2.1] heptanol, octahydropentalenol (octahydropentalenol), octahydro-1H-indenol (octahydro-1H-indenol) or a combination of two or more thereof. Alternatively, the cycloalkyl alcohol according to the embodiment can include the alcohol replaced by the cycloalkyl containing unsaturated bonds, or can include the structure in which the cycloalkyl is replaced by any substituent, without limitation. In addition, the above-mentioned cycloalkyl alcohol is only an example and is not limited, as long as it is the alcohol with cycloalkyl.

[0063] Another embodiment provides a Ziegler-Natta catalyst for polymerization of a low-density copolymer, which is prepared by using the method for preparing the Ziegler-Natta catalyst for polymerization of a low-density copolymer according to the embodiment.

[0064] Another embodiment provides a method for producing a low-density copolymer using the Ziegler-Natta catalyst for polymerization of a low-density copolymer according to the embodiment. Specifically, a method for producing a low-density copolymer is provided, the method comprising contacting an olefin monomer with the Ziegler-Natta catalyst for polymerization of a low-density copolymer according to the embodiment.

[0065] In one embodiment, the olefin monomer may be, for example, an olefin monomer having 2 to 20, 2 to 15, or 4 to 10 carbon atoms.

[0066] In one embodiment, the low density copolymer may be, for example, a linear low density copolymer, and may be, for example, a linear low density polyethylene.

[0067] In one embodiment, the density of the low density copolymer may be 0.91 g / mL to 0.94 g / mL, 0.912 g / mL to 0.938 g / mL, 0.915 g / mL to 0.935 g / mL, or 0.915 g / mL to 0.924 g / mL, but this is just an example and the density of the low density copolymer is not limited thereto. In one embodiment, the melt index (MI) of the low density copolymer can be 0.1 g / 10 min to 5.0 g / 10 min, 0.1 g / 10 min to 4.0 g / 10 min, 0.1 g / 10 min to 3.0 g / 10 min, 0.1 g / 10 min to 2.0 g / 10 min, 0.1 g / 10 min to 1.0 g / 10 min, 0.2 g / 10 min to 1.0 g / 10 min, 0.4 g / 10 min to 1.0 g / 10 min, or 0.5 g / 10 min to 0.9 g / 10 min when measured at about 190°C according to ISO 1133:1997 or ASTM D1238:1999, but this is just an example and the melt index of the low density copolymer is not limited thereto. DETAILED DESCRIPTION

[0068] Hereinafter, the embodiments and experimental examples are described in detail. However, the embodiments and experimental examples to be described below are only for explaining a part of the embodiment, and the technology described in this specification is not limited thereto.

[0069] <Example 1-1 to Example 1-4>

[0070] Into a 500 mL flask, 33 mL (30.0 mmol) of a 0.9 M heptane solution of ethyl n-butyl magnesium (BEM, [dialkyl magnesium]) was injected, and then 100 mL of n-heptane was injected. While stirring the solution, 3.50 g (15.0 mmol) of triethylaluminum (AlEt3, [aluminum compound-1]) was slowly added dropwise. Afterwards, isopropanol (i-PrOH, [alcohol]) was slowly added dropwise according to the equivalents shown in Table 1, and the reaction temperature was maintained at about 0°C to -30°C, and the reaction was fully carried out for about 4 hours, thereby preparing a 0.2 M magnesium carrier slurry solution.

[0071] 30 mL (6.00 mmol) of 0.2 M magnesium support slurry solution ([support]) was injected into a 100 mL flask, and 3.3 mL (0.40 mmol) of 5 wt% Ti(Oi-Pr)4 ([metal compound]) heptane solution was injected, and stirred for more than 4 hours. Then, 2 mL (2.00 mmol) of 1.0 M ethylaluminum dichloride solution (C2H5AlCl2, [aluminum compound-2]) diluted with hexane was injected, and stirred at room temperature for more than 6 hours to prepare a reddish-brown catalyst (Ziegler-Natta) solution.

[0072] <Example 2-1 to Example 2-4>

[0073] A reddish brown catalyst (Ziegler-Natta) solution was prepared in the same manner as in Example 1-1 to Example 1-4, except that [metal compound] was changed to 3.28 mL (0.40 mmol) of 5 wt % TiCl 4 heptane solution.

[0074] <Example 3-1 to Example 3-4>

[0075] A reddish brown catalyst (Ziegler-Natta) solution was prepared in the same manner as in Example 1-1 to Example 1-4 except that [Aluminum Compound-1] was changed to 2.97 g (15.0 mmol) of triisobutylaluminum (Al(i-Bu)3).

[0076] <Example 4-1 to Example 4-4>

[0077] A reddish brown catalyst (Ziegler-Natta) solution was prepared in the same manner as in Example 1-1 to Example 1-4, except that [alcohol] was changed to isobutyl alcohol (i-BuOH).

[0078] <Example 5-1 to Example 5-4>

[0079] A reddish brown catalyst (Ziegler-Natta) solution was prepared in the same manner as in Example 1-1 to Example 1-4, except that [alcohol] was changed to 2-methyl-2-propanol (t-BuOH).

[0080] <Example 6-1 to Example 6-4>

[0081] A reddish brown catalyst (Ziegler-Natta) solution was prepared in the same manner as in Example 1-1 to Example 1-4, except that [alcohol] was changed to cyclohexanol (CHN).

[0082] <Comparative Examples 1-1 to 1-4>

[0083] Into a 500 mL flask, 33 mL (30.0 mmol) of a 0.9 M heptane solution of ethyl n-butyl magnesium (BEM, [dialkyl magnesium]) was injected, followed by 120 mL of n-heptane. While stirring the solution, 2.97 g (15.0 mmol) of triisobutyl aluminum (Al(i-Bu) 3, [aluminum compound-1]) was slowly added dropwise. Afterwards, n-propanol (n-PrOH, [alcohol]) was slowly added dropwise in an equivalent amount as shown in Table 1, and the reaction temperature was maintained at about 0°C to -30°C, and the reaction was fully carried out for about 4 hours, thereby preparing a 0.2 M transparent magnesium carrier slurry solution.

[0084] 30 mL (6.00 mmol) of 0.2 M magnesium support slurry solution ([support]) was injected into a 100 mL flask, and 0.36 mL (0.34 g, 1.20 mmol) of Ti(Oi-Pr)4 ([metal compound]) heptane solution was injected, and stirred for more than 4 hours. Then, 24.00 mL (24.00 mmol) of 1.0 M ethylaluminum dichloride solution (C2H5AlCl2, [aluminum compound-2]) diluted with hexane was injected, and stirred at room temperature for more than 6 hours to prepare a brown catalyst (Ziegler-Natta) solution.

[0085] <Comparative Examples 2-1 to 2-4>

[0086] A catalyst (Ziegler-Natta) solution was prepared in the same manner as in Comparative Examples 1-1 to 1-4, except that [Aluminum Compound-1] was changed to triethanol (AlEt3).

[0087] <Comparative Examples 3-1 to 3-4>

[0088] A catalyst (Ziegler-Natta) solution was prepared in the same manner as in Example 1-1 to Example 1-4, except that [alcohol] was changed to n-butanol (n-BuOH).

[0089] [Table 1]

[0090]

[0091] 1) Dialkyl magnesium A: BEM

[0092] 2) Aluminum compound-1

[0093] B:AlEt3 / C:Al(i-Bu)3

[0094] 3) Alcohol

[0095] D:i-PrOH / E:i-BuOH / F:t-BuOH / G:CHN / H:n-PrOH / I:n-BuOH

[0096] [Table 2]

[0097]

[0098] 1) Metal compound J: Ti(Oi-Pr)4 / K: TiCl4

[0099] 2) Aluminum compound-2

[0100] L: C2H5AlCl2

[0101] <Experimental Example 1> Polymerization of low-density copolymer

[0102] Under a stable anhydrous nitrogen atmosphere, 0.5 L of a saturated hydrocarbon solvent (methylcyclohexane) was charged into an autoclave reactor, 0.2 g (0.15 mol) of triethylaluminum and 100 mL (70 g, 0.7 mol) of 1-octene were injected, the reactor temperature was raised to 180° C., stirring was performed, and then ethylene was injected into the reactor at 30 bar. 1.7 μmol of each catalyst prepared in Examples 1-4, 2-4, 3-4, 4-4, 5-4 and 6-4 and Comparative Examples 1-4 and 3-4 was diluted with 3 mL of a saturated hydrocarbon solvent (methylcyclohexane), the diluted catalyst was transferred to a catalyst port, and the catalyst port was pressurized to 50 bar with anhydrous nitrogen. After the inside of the autoclave reactor was saturated with ethylene, the catalyst was injected into the reactor from the catalyst port under isothermal conditions at 180° C., and semi-batch polymerization was performed for 10 minutes with continuous supply of ethylene. Afterwards, the reactant is recovered through the outlet, and the solvent is dried to obtain a linear low-density copolymer (linear low-density polyethylene (LLDPE)). The yield, catalyst productivity, melt index and density of the obtained linear low-density polyethylene are measured. The results are shown in Table 3.

[0103] At this time, the catalyst productivity is defined as a value obtained by dividing the mass of produced LLDPE by the mass of the catalyst. The melt index was measured by testing at 190° C. according to ASTM D1238 standard, and the density was measured using a density gradient column.

[0104] [Table 3]

[0105]

[0106] Referring to Table 3, it can be seen that, compared with the case where the catalyst prepared in the comparative example was used for polymerization, the yield of the copolymer was significantly increased when the catalyst prepared in the example was used for polymerization, and the catalyst productivity value was increased.

[0107] <Experimental Example 2> Crystallization Elution Fractionation (CEF)

[0108] In order to analyze the physical properties of the polymers prepared using the catalysts of Examples 1-4 by crystallization elution fractionation (CEF), a POLYMER-CHARCRYTEX-42 instrument and a trichlorobenzene (TCB) solution were used for testing. At this time, commercially available product A (Dow Chemical Company (DOWLEX 2045G), MI: 1.00 g / 10 minutes, density: 0.9200 g / mL) and commercially available product B (SK Chemicals Co., Ltd. (FN810), MI: 0.99, density: 0.9198 g / Ml) were prepared and tested as a comparative group. The results are as follows Figure 1 shown.

[0109] Through the above experiments, it can be confirmed that in the case of the polymer prepared using the catalyst of the embodiment, compared with the commercially available product, in the CEF spectrum, the proportion of the high-density region (homopolymer) at about 80°C to 100°C is low, and the proportion of the low-density region (copolymer) at about 50°C to 80°C is high. Therefore, it can be seen that the catalyst of the embodiment can effectively prepare a low-density copolymer with high elongation.

[0110] <Experimental Example 3> Analysis of the form of magnesium carrier solution

[0111] In order to analyze the transparency and solubility of the magnesium carrier solution according to the type of alcohol solvent, the forms of the magnesium carrier solutions prepared in the examples and comparative examples were observed. The results are shown in Table 4. Among them, photos of the magnesium carrier solutions prepared in Examples 1-4, Examples 3-4, Examples 4-4, Examples 5-4 and Examples 6-4, and Comparative Examples 1-4, Comparative Examples 2-4 and Comparative Examples 3-4 were taken. Photos are shown in Table 4. Figure 2 shown.

[0112] [Table 4]

[0113]

[0114] TS: Transparent solution OS: Opaque slurry

[0115] Table 4 and Figure 2It can be seen that the magnesium support solution prepared using branched alkyl alcohol or cycloalkyl alcohol as solvent is opaque, while the magnesium support solution prepared using straight-chain alkyl alcohol as solvent is transparent. It can be confirmed that in the preparation of magnesium support solution, alcohol solvent contributes greatly to the form of solution. Specifically, it can be seen that magnesium support with significantly stable physical properties can be prepared using branched alkyl alcohol substituted alcohols such as isopropyl, isobutyl or tert-butyl or cyclic alkyl substituted alcohols such as cyclohexane, and the magnesium support can be used to prepare highly active Ziegler-Natta catalysts for producing low-density copolymers.

[0116] Above, an embodiment is described in detail through preferred examples and experimental examples, but the scope of the embodiment is not limited to the specific embodiment, but should be explained according to the appended claims.

Claims

1. A method for preparing a Ziegler-Natta catalyst for the polymerization of a low density copolymer, comprising: adding a branched alkyl alcohol or a cycloalkyl alcohol to a mixture of dialkyl magnesium and a compound represented by the following Chemical Formula 1 to prepare a solution containing a magnesium carrier; as well as Adding a metal compound containing titanium (Ti) to the solution containing the magnesium support: [Chemical formula 1] R 1 x AlCl 3-x In Chemical Formula 1, Each R 1 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and x is 1 to 3.

2. The method according to claim 1, further comprising adding a compound represented by the following Chemical Formula 2 after adding the metal compound: [Chemical formula 2] R 2 y AlCl 3-y In chemical formula 2, Each R 2 Independently for C 1-10 Alkyl or C 3-10 cycloalkyl; and y is 1 to 2.

3. The method according to claim 1, wherein each R 1 Independently for C 1-6 Alkyl or C 3-6 Cycloalkyl.

4. The method according to claim 1, wherein the molar number of the branched alkyl alcohol or cycloalkyl alcohol added exceeds one time the molar number of the dialkyl magnesium. 5 . The method according to claim 1 , wherein the mole number of the branched alkyl alcohol or cycloalkyl alcohol added exceeds twice the mole number of the compound represented by Chemical Formula 1.

6. The method according to claim 2, wherein each R 2 Independently for C 1-6 Alkyl or C 3-6 Cycloalkyl.

7. The method according to claim 2, wherein the compound represented by Chemical Formula 2 is EtAlCl2, MeAlCl2, PrAlCl2, BuAlCl2 or (C2H5) 3 / 2 AlCl 3 / 2 . 8 . The method according to claim 2 , wherein a molar ratio of the metal compound to the compound represented by Chemical Formula 2 is 1:0.1 to 1:

15.

9. The method according to claim 1, wherein the molar ratio of the metal compound to the magnesium support is 1:5 to 1:

30.

10. The method according to claim 1, wherein the metal compound further contains a Group IV or Group V metal.

11. The method according to claim 1, wherein the metal compound contains TiX4 or (R 3 O) z Ti(X) 4-z , where X is a halogen atom, each R 3 Independently for C 1-10 The alkyl group, z is an integer from 1 to 4.

12. The method of claim 11, wherein the metal compound is a mixed metal compound further comprising a compound containing a Group V metal.

13. The method according to claim 1, wherein the branched alkyl alcohol is a branched C 3-10 Alkyl alcohol.

14. The method according to claim 1, wherein the branched alkyl alcohol is selected from one or a combination of two or more of isopropyl alcohol, isobutyl alcohol and tert-butyl alcohol.

15. The method of claim 1, wherein the cycloalkyl alcohol is C 3-10 Cycloalkyl alcohols.

16. The method of claim 1, wherein the cycloalkyl alcohol is cyclohexanol.

17. A Ziegler-Natta catalyst for the polymerization of a low-density copolymer, prepared by the method for preparing a Ziegler-Natta catalyst for the polymerization of a low-density copolymer according to any one of claims 1 to 16.

18. A method for producing a low-density copolymer, comprising contacting an olefin monomer with the Ziegler-Natta catalyst for polymerization of a low-density copolymer as claimed in claim 17.

19. The method according to claim 18, wherein: The low density copolymer has a density of 0.91 g / mL to 0.94 mL, and a melt index (MI) of 0.1 g / 10 min to 5.0 g / 10 min when measured according to ASTM D1238.

Citation Information

Patent Citations

  • Ziegler-Natta catalyst

    US8003741B2